PREVENTION OF STUNTING THROUGH STRENGTHENING PARENTING BEHAVIORS AND FAMILY RESILIENCE: SYSTEMATIC REVIEW - Dina Istiana; Firnanda Erindia; Yura Witsqa Firmansyah; Fitriatul Jannah; Hilda Dea Revani; Eileen Savage (SYNTHESIS Global Health Journal, 2025)
Background. Stunting remains one of the most serious public health problems in Indonesia. This condition describes linear growth failure in children due to chronic malnutrition, especially during the first 1000 days of life (the first day of birth), which has a long-term impact on children's physical and cognitive development and future productivity. This study aims to identify various implementations of stunting prevention interventions. Research Method. Articles were searched using three databases: Web of Science, Google Scholar, and ProQuest. The inclusion criteria for this study were articles published within one year, from 2024 to 2025, with free access. The research method used in this study was a systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Findings. it was found that stunting prevention in Indonesia is influenced by various multidimensional factors, including parenting, knowledge, behavior, and the social and economic conditions of the family. Conclusion. Based on the articles reviewed, Stunting prevention needs to be carried out through a holistic and intersectoral approach, including education, family empowerment, improving the nutritional quality of pregnant women, cadre support, and the use of technology and sustainable food policies.